"Sistemas administrativo, pesaje y determinación de humedad en productos para casas comerciales agrícolas" - Cornejo Velásquez, Lisesth Marianela (2014)
Historically agricultural business houses in our country have used manual methods to the process of calculating prices paid to farmers who deliver their products. It is also known that in determining the mechanical weight scales, they are more susceptible to errors of weight change are used. Depending on the amount of moisture present in the grains of agricultural products, in most cases must deduct a percentage of the price that should be paid, this is normally done by simple observation to determine the amount of moisture present, generating disagreement in whom bring their products to sell. This research work presents a possible solution, proposing the use of an electronic scale and a humidity sensor, having communication with a computer through a small desktop application for more accurate data, reducing calculation errors. Thus it is expected that farmers and traders have more confidence and there is no discrepancy in the negotiation. Through the development of a web system, is able to manage the information generated in the process of buying and selling allowing the manager/administrator of the trading house to generate reports for better decision making. Farmers also provide ease of use a quotation of prices estimated by allowing them the money they receive for their products. They also have the option to separate shifts to get their products on the specific date and time by avoiding wasted time queuing.